Information Technology Management System of Sharing Knowledge Between Universities Using Systematic Literature Review - Fernando, Ricky; Sama, Hendi (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
Knowledge is a vital resource for academic institutions, driving innovation dan development. However, universities face challenges in effective knowledge sharing due to cultural barriers, lack of trust, and technological constraints. This research, conducted using a Systematic Literature Review (SLR), identifies key variables influencing knowledge sharing, highlights challenges, and proposes solutions to foster collaboration. The findings reveal that cultural barriers, such as competitive organizational environments and technological constraints, including high costs and user-friendly systems, significantly hinder knowledge sharing. To address these issues, the study recommends implementing user-friendly technologies, promoting collaboration through seminars and workshops, and encouraging cross-departmental projects. These solutions provide actionable insights to enhance knowledge sharing frameworks and support innovation across academic institutions